Why Is Recreational Hunting a Moral Evil? - Szklarska, Anna (ETHICS IN PROGRESS, 2020)
The paper reviews the recent book edited by Dorota Probucka, entitled The Ethical Condemnation of Hunting (in Polish: Etyczne potępienie myślistwa), Universitas Press, Kraków 2020, pp. 426. Probucka is one of the most prominent Polish experts in animal studies, especially in applied ethics and the field of animal rights (e.g., Probucka 2018a, 2018b, 2017). The discussed monograph encompasses the contributions of 19 authors representing 9 universities from Poland and abroad. Their core issue of consideration was the topical problem of hunting, examined from various perspectives: ethical and legal, psychological, social and cultural, both on the theoretical level and in relation to the practice of hunting. This review focuses on the core arguments against hunting and discusses them in detail. The Ethics in Progress journal had the honour of contributing to the media patronage of Dorota Probucka’s et al. edition.